The impact of financial development, oil price on economic growth in African OPEC members - Umar, Bala; Lee, Chin; Kaliappan, Shivee Ranjanee; Ismail, Normaz Wana (ASERS Publishing, 2017)
This study ascertains impacts of financial development, oil price on economic growth in African OPEC members. Many studies have been done on financial development and economic growth, without considering the nature of the economic dependency. This study considered the African OPEC members has oil-dependent economies. The study used dynamic panel method in the estimation of the results. The four sample countries are Algeria, Angola, Libya, and Nigeria the study excluding Gabon has suspended it OPEC membership within the study period. The panel cointegration estimated results using Pedroni cointegration procedure indicate that there is a long-run relationship in models. The long-run coefficient using modified OLS (FMOLS) estimator provide substantial evidence that financial development, oil price are positively encouraged economic growth. From the results, we observed that the economy is highly benefiting from oil price models without investment, but when investment included in the model, the impact of oil price become less. The policy implications of these results are that even though the economy is benefiting oil price but because of the uncertainty in the oil market the policy makers should encourage the financial sector credit to productive investment industries that can support economic growth to reduce the oil dependency to diversify the economic activities.